Influence of Gender, Emotional and Spiritual Intelligence on the Level of Accounting Understanding - Ayu Indira Dewiningrat; Jonathan Jacob Paul Latupeirissa (Journal of Humanities, Social Science, Public Administration and Management (HUSOCPUMENT), 2021)
Understanding of accounting is someone who is clever and understands accounting properly. Accounting is a process of recording, classifying, summarizing, processing and presenting data, transactions and events related to finance so that it can be used by people who use it easily understood for making decisions and for other purposes. This study aims to determine the effect of gender, emotional intelligence and spiritual intelligence on the level of accounting understanding of students majoring in accounting at private universities in the city ​​of Denpasar. Samples were taken by purposive sampling technique as many as 376 accounting students. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the gender variable affects the level of accounting understanding with a significance value of 0.000 < 0.05 , the emotional intelligence variable has no effect on the level of accounting understanding with a significance value of 0.74> 0.05, the spiritual intelligence variable has no effect on the level of understanding. Accounting with a significance value of 0.663> 0.05.